2020
DOI: 10.1007/s43388-020-00006-1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality determines bird abundance, richness, and diversity among contrasting forest environments in the Northern Pantanal

Abstract: Seasonally flooded ecosystems are comprised by heterogeneous vegetation mosaics (i.e., environments), wherein habitat availability and food resources are spatially and temporally variable. Overall, these factors determine the abundance, richness, and diversity of birds. To evaluate season-and environment-dependent bird abundance, richness, and diversity, we sampled understory birds along two seasons (dry and wet) in three forest environments, i.e., one semideciduous non-flooding forest (Cordilheira) and two ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Thus, abundance and behaviour may better capture some important characteristics of bird populations and communities facing seasonality in the Pantanal. Indeed, abundance is a well-documented measure to determine differences in bird populations between the dry and the flooding season in this biome (Pinho & Marini 2012, Thomas et al 2020. By contrast, process-related responses such as interspecific interactions (e.g.…”
Section: Assessment Of Research Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, abundance and behaviour may better capture some important characteristics of bird populations and communities facing seasonality in the Pantanal. Indeed, abundance is a well-documented measure to determine differences in bird populations between the dry and the flooding season in this biome (Pinho & Marini 2012, Thomas et al 2020. By contrast, process-related responses such as interspecific interactions (e.g.…”
Section: Assessment Of Research Biasmentioning
confidence: 99%
“…Amazonia, Cerrado and Chaco) supplies diverse habitat and food resources, which ultimately determine the breeding season, abundance and diversity of birds (Pinho & Marini 2012, Pinho et al 2017, Thomas et al 2020. However, few studies have described the spatial and temporal dynamics of Pantanal bird communities (Figueira et al 2006, Donatelli et al 2017 or aspects related to behaviour, reproduction and conservation of species (Yabe 2009, Yabe et al 2011, Pinho & Marini 2012, Pinho et al 2017, Thomas et al 2020. In recent decades, the spread of pastures for cattle, soy production and the introduction of exotic species have increased the rates of fragmentation and native habitat loss in the Pantanal by about 11% (MapBiomas 2017, Tomas et al 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the ecosystem functions of birds in wetlands are often overlooked due to the lack of essential information on their interactions in these environments (Green and Elmberg 2013). Some studies conducted in the Pantanal demonstrated the importance of environmental heterogeneity and seasonality for the diversity of plants (Catian et al 2018;Olivo-Neto et al 2020), mammals (Lázari et al 2013), birds (Deus et al 2020, Thomas et al 2020, snakes (Piatti et al 2019), anurans (Pansonato et al 2011), fish (Penha et al 2017) and invertebrates (Aranda and Aoki 2018;Battirola et al 2018). Nevertheless, due to recurrent environmental changes, there are still gaps in the understanding of events related to seasonality in species diversity (Tonkin et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, the ecosystem functions of birds in wetlands are often overlooked due to the lack of essential information on their interactions in these environments (Green and Elmberg 2013). Some studies conducted in the Pantanal demonstrated the importance of environmental heterogeneity and seasonality for the diversity of plants (Catian et al 2018;Olivo-Neto et al 2020), mammals (Lázari et al 2013), birds (Deus et al 2020, Thomas et al 2020, snakes (Piatti et al 2019), anurans (Pansonato et al 2011), fish (Penha et al 2017) and invertebrates (Aranda and Aoki 2018;Battirola et al 2018). Nevertheless, due to recurrent environmental changes, there are still gaps in the understanding of events related to seasonality in species diversity (Tonkin et al 2017).…”
Section: Introductionmentioning
confidence: 99%